TEACHER COMPETENCE IN QUR’ANIC PERSPECTIVE: (STUDY OF QS. AL-‘ASHR/103: 1-3) - Tri Yugo (Takafu: Journal of Tafsir and Gender Perspective, 2024)
In carrying out their duties as educators in schools, teachers bear a large burden. An experienced teacher is expected to be able to carry out his responsibilities in the learning process with enthusiasm and fun. Reality shows that the learning process in schools is often considered boring and ineffective, so educational goals are not achieved. This research aims to examine the meaning and essence that emerge from the QS. Al-’Ashr verses 1–3 by considering the opinions of commentators regarding the value or education-related content of the QS. Al-’Ashr verses 1-3, regarding the importance of time, faith, good deeds, and behaving in truth and patience in the formation of teacher competence. This research uses a library research style, and Tahlili interpretation is used in this research. The results show that teacher competence from the Surat Al-Ashr perspective involves managing time wisely, understanding students' potential and needs, instilling the value of faith, supporting holistic growth, providing positive advice, and maintaining patience in educating.